Research methods for sports studies - Jones, Ian, 1970 (Routledge, 2022)
"Research Methods for Sports Studies is a comprehensive, engaging and practical textbook that provides a grounding in qualitative and quantitative research for students studying programmes related to sport and physical activity. Leading the reader step-by-step through the entire research process, from identifying a research question and collecting and analysing data to writing and presenting the research report, it is richly illustrated throughout with sport-related case studies and examples from around the world. Research Methods for Sports Studies is designed to be a complete and self-contained companion to any research methods course, and contains a wealth of useful features, such as highlighted definitions of key terms, all new case studies from active researchers, and practical research exercises. Now in a revised and updated fourth edition, and in full colour for the first time, the book features expanded coverage of key topics such as online research, data visualisation, image analysis, source evaluation, mixed methods, and the philosophical foundations of research. It also includes new material on the challenges of researching during a pandemic, and reflects on the importance of diversity and inclusion, from feminist and indigenous methodologies to increased diversity of cases and researcher voices. This is an essential read for any student undertaking a dissertation or research project as part of their studies in sport, exercise and related fields, including sport management, sport development, the sociology of sport, sports marketing, sport-related tourism, sport coaching, physical education, and other similar degrees. Additional online material is available for students and instructors, including web links, multiple choice revision questions, PowerPoint slides and additional learning activities for use in and out of class"--